A new discrete method for solution to consolidation problem of ground with vertical drains subjected to surcharge and vacuum loadings. Issue 4 (21st November 2019) - Nghia-Nguyen, Trong; Shukla, Sanjay Kumar; Nguyen, Dang Dinh Chung; Lam, Le Gia; H-Dang, Phuoc; Nguyen, Phu-Cuong
Abstract : Purpose: This paper aims to present a new discrete method to predict average excess pore pressure and degree of consolidation for soft ground using prefabricated vertical drains under time-dependent surcharge and/or vacuum loading and multi-soil layers. Design/methodology/approach: The drain is discretized into a number of mesh points at which the average excess pore pressure is estimated. The conventional Laplace technique is used to solve the analytical equations. The proposed method is validated with previous findings reported in the literature. Moreover, field measurements are used to verify the accuracy of the proposed method with a case history of ground improvement by prefabricated vertical drains using the vacuum consolidation technique. Findings: In comparison to past studies, this new discrete method is simpler to be implemented in a spreadsheet calculation to achieve a rational solution with less computational time for similar consolidation problems. Moreover, the current approach also incorporates a solution for multi-soil layers, which can hardly be derived by analytical solutions. Originality/value: According to authors' knowledge, this is the first-time discrete method by Laplace transform technique is applied for the vertical drain.